Adsorption of Lead on Cucumber Peel. (10th May 2017) - Basu, Mousumi; Guha, Arun K.; Ray, Lalitagauri
Abstract: The competency of cucumber peel (CP) was explored for adsorption of lead. Optimum adsorption occurred at pH 5.0 and at incubation temperature of 30 °C. The process of adsorption was quite fast to be completed within a time frame of 60 min obeying pseudo second order rate kinetics. 1.0 g sorbent was capable enough to adsorb 133.60 mg lead (qmax ) with Langmuir isotherm model categorically illustrating the adsorption process. The magnitude of hindrance exerted by cadmium in binary system as a consequence of co-ion effect was found to be rather insignificant. Functional group modification study confirmed principal role of carboxyl group in metal binding. The biomass was characterized by different instrumental analyses like TGA, SEM, EDAX, XRD, FTIR and zeta potential measurement which additionally authenticated the sorption phenomenon. Post adsorption elution of the loaded metal was successfully executed using HCl as eluant. Graphical abstract: Highlights: Cucumber peel (CP) was employed as a successful sorbent for lead adsorption. Adsorption was optimum at pH 5.0 and completed within 60 min obeying pseudo second order rate kinetics. Adsorption data best fitted to Langmuir isotherm model. Uptake of lead was almost unhindered even in presence of cadmium in binary system. Carboxyl group was the primary metal binding group.